Indexing chemical structures: Exemplified compound indexing in patents by the vendors Thomson Reuters, Chemical Abstracts and Elsevier – A comparative study by the Patent Documentation Group (PDG). (March 2016) - Ede, Mark; Endacott, John; Harper, Mark; Rees, David
Abstract: The following article briefly discusses the history of the PDG and why Taskforce/Working Group efforts have been an important part of PDG activities. The authors describe a methodology for analysing exemplified compound indexing from the patent literature in three databases: Chemical Abstracts (CAPLUS and REGISTRY), Derwent World Patents Index (DWPI) and Reaxys. This article also discusses the post analysis feedback from the database vendors. The feedback and the further discussions with the vendors culminated in some examples of positive changes to their indexing policies.